The Prevalence of a Bonding Strategy in Covid-19 Response Networks: Explaining Intermunicipal Partnering in the Santiago Metropolitan Region, Chile - Arias-Yurisch, K (Routledge, 2024)
COVID-19, with its spatial particularities, has challenged the governance of institutionally fragmented regions, obliging local governments to respond collaboratively. While intermunicipal collaboration is expected, little is known about partnering strategies. Based on the institutional collective action framework, this article explains which partnering strategies (bonding or bridging) have prevailed in the city of Santiago. Using exponential random graph models, it reveals a tendency to transitive clustering, socio-territorial homophily and the importance of planned emergency intermunicipal networks. The findings demonstrate the prevalence of bonding and an absence of bridging, measured by both endogenous and exogenous factors, with implications for effective regional response. © 2022 Regional Studies Association.